APPLICATION OF INNOVATIVE, INFORMATION, COMMUNICATION AND COMPUTER TECHNOLOGIES AND TEACHING TOOLS FOR CONDUCTING VOCATIONAL TRAINING CLASSES - Petrishena, Olena (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
The application of innovative, information and communication and computer technologies and teaching aids for conducting professional training classes is disclosed.